พฤติกรรมไตรโบโลยีของเหล็กกล้าไร้สนิมและวาเนเดียมคาร์ไบด์ที่เคลือบด้วยกระบวนการทีอาร์ดี - ชาญเชาว์ เลิศล้ำมีชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
In this research, vanadium carbide coating by TRD process was conducted on tool steel disc and intentionally tempered in air to produce thicker vanadium oxide on vanadium carbide surface. Ring-on-disc wear test was conducted by sliding with austenitic stainless steel ring to investigate tribological behavior. Wear test was conducted with sliding distance of 2000 m. Sliding velocity was 1.432 m/s. Normal load was varied from 120 N till 320 N. Weight of ring was measured before and after wear tests. Chemical composition of ring surface was cross-section analyzed by the EPMA. Surface of the disc was analyzed by the XPS. Wear test results showed that weight loss of stainless steel increased with increasing normal load from 120 N till 320 N. The EPMA analysis result of cross-section of ring showed that ring surface contained more Cr content than Fe content in surface oxide in specimen with 120 N load while more Fe content than Cr content was shown in that with 320 N load. Cr rich oxide on stainless steel surface contributed to lower weight loss of stainless steel ring. The XPS result of disc surface before and after wear tests showed V2O5 on VC coating surface which contributed to less adhesion of stainless steel on VC coated disc.